Limb girdle muscular dystrophy R12 (LGMD 2L, anoctaminopathy) mimicking idiopathic inflammatory myopathy: key points to prevent misdiagnosis. (15th July 2021) - Marago, Italo; Roberts, Mark; Roncaroli, Federico; DuPlessis, Daniel; Sewry, Caroline; Nagaraju, Santhosh; Limbada, Faheema; Marini-Bettolo, Chiara; Hudson, Judith; Banerjee, Siwalik; Newton, Laura; Bukhari, Marwan; et al.
Abstract: Objectives: Diagnosing the idiopathic inflammatory myopathies (IIMs) can be challenging as several conditions, including genetic myopathies such as limb girdle muscular dystrophy type R12 (LGMD 2 l, anoctaminopathy) mimic the presentation. Here we describe learning points identified from review of four patients with LGMD 2 l who were initially incorrectly diagnosed with IIM. Our aim is to provide clinicians working in adult rheumatology services with a toolkit to help identify non-inflammatory presentations of myopathy. Methods: We performed retrospective review of medical notes, laboratory results, muscle imaging and histological findings of four patients with LGMD 2 l who were previously misdiagnosed with IIM. We focussed on clinical presentation and progression, therapeutic agents used and events leading to revision of the diagnosis. Results: Three male patients and one female patient with a mean age of 51 years at presentation were reviewed. In each case, treatment with immunosuppressants, in one case for >15 years, was observed without a clear therapeutic response. All patients were negative for anti-nuclear antibodies and available myositis-associated/specific autoantibodies and associated connective tissue disease features were absent. Prominent fatty infiltration and selective muscle involvement on thigh MRI was found in common. Conclusions: Adult-onset genetic myopathies, particularly LGMD R12, can mimic IIM. Accurate diagnosis is crucial to avoid the use of potentially harmful immunosuppressive therapies, to allow appropriate genetic counselling and to facilitate involvement in research studies.